Czynniki wpływające na efektywność gospodarowania małych przedsiębiorstw działających na rynku dóbr przemysłowych - Glinkowski, Czesław; Nowak, Dariusz (Factors Influencing the Effectiveness of Management of Enterprises Operating on the Industrial Goods Market, 2005)
In the paper there are presented factors which have an effect on the effectiveness of management of enterprises operating on the industrial goods market. These factors are divided into three groups: standard-factors, professional factors and partner factors. The suppliers achieving superior segments of the market, cooperating with more and more up-to-date enterprises are forced to take into account particular groups of factors. The deficiency in taking into account of these elements may contribute to the loss of the standing and the market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 107-115